Can models of evolutionary transition clarify the debates over the Neolithic Revolution?. (13th March 2023) - Shavit, Ayelet; Sharon, Gonen
Abstract : The 'Neolithic Revolution, ' sometimes referred to as the emergence of agriculture at its earliest in the southern Levant, is the most significant shift in human history, shaping the world we live in today. Yet, after 100 years of study, its major cause, tempo (gradual or revolutionary), and impact of human intentionality remain disputed. Here, we examine the research potential of an evolutionary transition in individuality (ETI) to clarify this dramatic shift. Applying an ETI research perspective reveals how different causes and conditions lead to the same result, enabling a holistic view rather than a reduction of 'Neolithic' to 'agriculture, ' or to one major climatic condition, inheritance system or standard evolutionary model, thus allowing us to clarify and bypass some of these heated, unresolved disputes. Additionally, unlike current archaeological emphasis on 'where, ' 'when, ' 'why' and 'how' questions, the ETI perspective offers a productive path for resolving a fundamental preliminary anomaly: why and how could the Neolithic lifeway evolve at all, given the selfish interest of individuals in a hunter–gatherer group? We do not intend to solve the shift to Neolithic lifeways, only to offer a fresh lens for examining it, emphasizing the relevance of tracking within and between group differences. This article is part of the theme issue 'Human socio-cultural evolution in light of evolutionary transitions'.